Implications of compromised zinc status on bone loss associated with chronic inflammation in C57BL/6 mice - Chongwatpol P; Rendina-Ruedy E; Stoecker BJ; Clarke SL; Lucas EA; Smith BJ (Dove Medical Press, 2015)
Pitipa Chongwatpol, Elizabeth Rendina-Ruedy, Barbara J Stoecker, Stephen L Clarke, Edralin A Lucas, Brenda J Smith Department of Nutritional Sciences, Oklahoma State University, Stillwater, OK, USA Abstract: Compromised zinc status and chronic inflammation are independent factors that can contribute to bone loss. However, zinc's role in regulating lymphoid and myeloid cell populations, combined with the interplay between the immune and skeletal systems raises the question as to the extent to which a low-grade inflammatory challenge in the context of marginal zinc deficiency would exacerbate bone loss. To address this question, young adult C57BL/6 male mice (n=32) were used in a 2×2 factorial design with dietary zinc (adequate or 35 ppm vs inadequate or −Zn =5 ppm) and lipopolysaccharide (LPS, 0 or 0.1 mg/kg body weight). Mice were fed their respective diets for 10 weeks. On the 6th week, mice had a slow release pellet implanted to induce a low-grade inflammation for the final 4 weeks of the study. −Zn induced a decrease in total white cell counts and peripheral lymphocytes, whereas LPS increased blood monocytes. LPS significantly reduced spine bone mineral density and trabecular bone volume and number of the vertebral body compared with both zinc adequate and inadequate without LPS groups. Likewise, the most pronounced effects on bone strength occurred with LPS, however, −Zn also had negative effects on the bone von Mises stresses. LPS induced an increase in TNF-α and this response was further increased with −Zn. Although the marginal zinc deficiency altered immune function, bone loss was not exacerbated with low-grade chronic inflammation in marginally zinc-deficient young adult mice. These findings demonstrate that in young adult animals an immune challenge modestly increases the inflammatory response and worsens bone biomechanics in the context of a marginal zinc deficiency, but not to the extent that more severe adverse outcomes are observed on bone structural parameters. Keywords: chronic inflammation, zinc deficiency, osteoporosis